2000
DOI: 10.1046/j.1523-5378.2000.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Metronidazole to Rabeprazole‐Amoxicillin‐Clarithromycin Regimen for Helicobacter pylori Infection Provides an Excellent Cure Rate with Five‐Day Therapy

Abstract: The simple twice-daily and short-term quadruple regimen for only 5 days provided an excellent eradication rate. Compliance with the regimen was high, and serious adverse effects were few. Therefore, the RACM regimen can be considered as safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 25 publications
3
38
1
Order By: Relevance
“…In the present study, there was not significant relationship between the H. pylori eradication rate and gender in any of the therapeutic groups. The result of current research is similar to the results of Khalilian et al, 17 and Chan et al, Studies 19 . In the present study, education level and smoking were also examined and no relationships were observed between education level, smoking and the H. pylori eradication rate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, there was not significant relationship between the H. pylori eradication rate and gender in any of the therapeutic groups. The result of current research is similar to the results of Khalilian et al, 17 and Chan et al, Studies 19 . In the present study, education level and smoking were also examined and no relationships were observed between education level, smoking and the H. pylori eradication rate.…”
Section: Discussionsupporting
confidence: 91%
“…In the studies of Khalilian et al, 17 and Naghara et al, 18 no significant relationship between the age groups and the treatment success of H. pylori was observed. In the present study, there was not significant relationship between the H. pylori eradication rate and gender in any of the therapeutic groups.…”
Section: Discussionmentioning
confidence: 89%
“…It consists of all four drugs (the PPI, clarithromycin, metronidazole/ tinidazole, and amoxicillin being given b.i.d.. The duration has ranged from 3 to 7 days and it has resulted in Grade B results similar to those obtained with sequential therapy [59][60][61][62][63][64][65][66][67] ( Figure 3). As with sequential therapy, studies are needed to test whether extending the duration of therapy will improve the results.…”
Section: Treatment Recommendations For Initial Treatmentmentioning
confidence: 99%
“…From reference 14 , with permission. Weight mean and 95% confidence intervals for 16 studies of sequential therapy (n = 1805) for 10 days(modified intention-to-treat) 57 and 9 studies of concomitant therapy (n = 715) ranging from 3 to 7 days (intention-to-treat) [59][60][61][62][63][64][65][66][67] .…”
Section: Key Pointsmentioning
confidence: 99%
“…8 It has a very potent and long-acting antisecretory property, and a greater antibacterial effect than either omeprazole or lansoprazole. 9 Although rabeprazole 20 mg/day seems to effectively eradicate H. pylori infection in a Japanese population, [10][11][12][13][14] only three of the studies directly investigated the comparative efficacy of 20 and 40 mg/day of rabeprazole. 10,13,14 The dosage of clarithromycin used in all these trials was 200 mg b.d., and the cure rate varied from 85 to 94%.…”
Section: Introductionmentioning
confidence: 99%